Tradisi Metirangga pada Masyarakat Suku Tolaki di Kelurahan Nambo Kecamatan Nambo Kota Kendari - lala andriani lestari; Rahmat Sewa Suraya; La Ode Marhini (LISANI: Jurnal Kelisanan, Sastra, dan Budaya, 2023)
The purpose of this study was to describe the implementation process and analyze the symbolic meaning of the tools and materials used in the implementation of the Metirangga tradition. The results of the study showed that the Metirangga tradition is still carried out now and the process of implementing the Metirangga tradition consists of (1) the preparation stage, the family first prepares the requirements for tools and materials such as pillows, seven sarongs, banana leaves, plates, henna leaves, powder, oil and water. and prepare the bride and groom by making them look beautiful and handsome. (2) the implementation stage, first; completing the Al-Quran, second; reciting the prophet Muhammad SAW, reciting the prophet's shalawat is also marked as the time when the Metirangga tradition ritual will be carried out, when the parents stand at that time the person appointed and trusted by the family will come forward to perform the Metirangga tradition ritual on the bride and groom. Fourth; the joint prayer that is combined after the reciting the bersanji is a form of joint prayer that is followed by the family and relatives. (3) the final stage is a joint meal and greetings to the bride and groom. The tools and materials used contain symbolic meanings: 1) pillows, in addition to functioning as a base in the first arrangement, also contain symbolic meanings, namely throne or honor. 2) seven sarongs) contain symbolic meanings, namely fortune. 3) banana leaves contain symbolic meanings, namely cold. 4) henna leaves contain symbolic meanings, namely harmony. 5) powder contains symbolic meanings, namely pure white. 6) oil contains symbolic meanings, namely slippery. 7) water contains symbolic meanings, namely cleansing. 8) plates contain symbolic meanings, namely respect.